2014
DOI: 10.2113/gsjfr.44.3.316
|View full text |Cite
|
Sign up to set email alerts
|

Test Fusion in Adult Foraminifera: A Review With New Observations of an Early Eocene Nummulites Specimen

Abstract: In foraminifera, so-called "double tests" usually arise due to abnormal growth originating mainly from twinning, but may also be caused by irregularities in the early chambers and by regeneration after test injury that modifies the direction of growth. A fourth cause of double tests has only rarely been reported: the fusion of the tests of two adult individuals. We studied an early Eocene Nummulites double test consisting of two adult individuals that fused after an extended period of independent growth. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…The occurrence of unusual ("abnormal") test morphologies in larger benthic foraminifera may have different origins, for example, the occurrence of plurilocular embryonic apparati, recoveries after test damage (e.g., predation, mechanical fracture), or fusion ("conjoined") (e.g., Hageman & Kaesler, 2002;Culver & Lipps, 2002;Ferràndez-Cañadell et al, 2014;Briguglio et al, 2016). Extreme environmental conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of unusual ("abnormal") test morphologies in larger benthic foraminifera may have different origins, for example, the occurrence of plurilocular embryonic apparati, recoveries after test damage (e.g., predation, mechanical fracture), or fusion ("conjoined") (e.g., Hageman & Kaesler, 2002;Culver & Lipps, 2002;Ferràndez-Cañadell et al, 2014;Briguglio et al, 2016). Extreme environmental conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Briguglio et al (2016) reported the occurrence of at least 16 embryos in one adult specimen of modern Cycloclypeus Carpenter. For further details about the causes and mechanisms of twin embryo development see Ferràndez-Cañadell et al (2014) and Benedetti (2015). Pluriembryonal embryonic apparati have been observed in Paleozoic fusulinids (Wilde, 1965), mid-Cretaceous alveolinids (Hottinger, 1974;Özgen-Erdem et al, 2003;Mathieu et al, 2011), Upper Cretaceous-Paleogene orbitoidal larger foraminifera (orbitoidids, orthophragminids, lepidocyclinids) (Meriç, 1964(Meriç, , 1970(Meriç, , 1971(Meriç, , 19731992;Omana et al, 2012;Bene-detti, 2015), and recent taxa such as Cycloclypeus (Briguglio et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Hard X-ray microtomography (µCT) has experienced enormous progress in efficient 3D imaging with micrometer resolution and has been increasingly recognized as an indispensable tool by paleontologists (Cunningham et al, 2014;Hoffmann et al, 2014). Owing to the true micrometer resolution, the non-destructive technique is increasingly applied in micropaleontology, paleoceanography and other fields of earth sciences (Speijer et al, 2008;Abel et al, 2012;Görog et al, 2012;Masschaele et al, 2007;Briguglio et al, 2011;chapter 6 in Branson, 2014;Briguglio et al, 2013;Ferràndez-Cañadell et al, 2014;Briguglio et al, 2016;Schmidt et al, 2013;Johnstone and Barker, 2010;Cnudde and Boone, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…One solution to the foraminiferal size issue is micro-X-ray computed tomography (CT), which also provides information on internal structures. Micro-X-ray CT has been used to assess attributes regarding foraminiferal tests (shells), such as biometry (Speijer et al 2008;Briguglio et al 2011Briguglio et al , 2013Hohenegger and Briguglio 2012;Ferrández Cañadell et al 2014) and test-wall dissolution by means of X-ray attenuation (Johnstone et al 2010;Iwasaki et al 2015). Nomaki et al (2015) applied X-ray CT to foraminiferal cells prepared for TEM (i.e., resin embedded; stained with heavy metals).…”
Section: Introductionmentioning
confidence: 99%